The Drosophila U1-70K protein is required for viability, but its arginine-rich domain is dispensable. - Salz, Helen K; Mancebo, Ricardo S Y; Nagengast, Alexis A; Speck, Olga; Psotka, Mitchell; Mount, Stephen M (Genetics, 2004)
The conserved spliceosomal U1-70K protein is thought to play a key role in RNA splicing by linking the U1 snRNP particle to regulatory RNA-binding proteins. Although these protein interactions are mediated by repeating units rich in arginines and serines (RS domains) in vitro, tests of this domain's importance in intact multicellular organisms have not been carried out. Here we report a comprehensive genetic analysis of U1-70K function in Drosophila. Consistent with the idea that U1-70K is an essential splicing factor, we find that loss of U1-70K function results in lethality during embryogenesis. Surprisingly, and contrary to the current view of U1-70K function, animals carrying a mutant U1-70K protein lacking the arginine-rich domain, which includes two embedded sets of RS dipeptide repeats, have no discernible mutant phenotype. Through double-mutant studies, however, we show that the U1-70K RS domain deletion no longer supports viability when combined with a viable mutation in another U1 snRNP component. Together our studies demonstrate that while the protein interactions mediated by the U1-70K RS domain are not essential for viability, they nevertheless contribute to an essential U1 snRNP function.
Keywords: Amino Acid Sequence; Animals; Animals, Genetically Modified; Arginine; Drosophila; Drosophila Proteins; Molecular Sequence Data; Mutation; Protein Structure, Tertiary; Ribonucleoprotein, U1 Small Nuclear; RNA-Binding Proteins